Environmental factors determining the distribution patterns of invasive Raphidiopsis raciborskii and R. mediterranea in central east Europe - Kokociński, Mikołaj; Graco-Roza, Caio; Jasser, Iwona; Karosienė, Jūratė; Kasperovičienė, Jūratė; Kobos, Justyna; Koreivienė, Judita; Mankiewicz-Boczek, Joanna; Soininen, Janne; Szczurowska, Agnieszka (Frontiers in Microbiology, 2025)
ObjectiveIn recent decades, the invasive cyanobacteria Raphidiopsis raciborskii and Raphidiopsis mediterranea have expanded their distribution globally, particularly in temperate regions. Understanding the ecological drivers of Raphidiopsis distribution is imperative to addressing the challenges associated with these species. Here, we aimed to characterize the distribution and biomass of R. raciborskii and R. mediterranea across 112 lakes in Poland and Lithuania in relation to local and regional factors.Research design and methodsIntegrated water samples were collected from 102 Polish and 10 Lithuanian lakes from different regions for phytoplankton and chemical analyses. The lakes varied in surface area, and exhibited diverse mixing regimes, trophic states, and morphometries. Phytoplankton was identified and quantified using a Fuchs-Rosenthal or Nageotte chamber. Additionally, we characterized the degree of human pressures the climatic constraints experienced by each lake.ResultsR. raciborskii occurrence has increased in eastern regions of Poland but biomass is relatively low compared to western Poland, likely due to lower air temperatures and nutrient concentrations, especially phosphorus. In contrast, R. mediterranea only occurred in a small number of lakes in Poland, and in a single lake in Lithuania, with no relation to measured local and regional variables.ConclusionsOur study shows contrasting patterns in the distribution of two invasive cyanobacteria species in Europe, highlighting the importance of climate and nutrients to the distribution of R. raciborskii, the most widespread species, and providing relevant information for decision making and conservation strategies.